Pengujian Black Box Testing pada Aplikasi Inventori Barang Berbasis Web di PT. AINO Indonesia - Ahmad Fahrezi; Fahry Noer Salam; Gilang Mahardhika Ibrahim; Rifki Rahman Syaiful; Aries Saifudin (Shofanah Media Berkah, 2022)
Inventori application belonging to PT. Aino Indonesia is an application used by the warehouse department to record all incoming and outgoing goods. If an error occurs in this application, it will cause big problems for the warehouse because the recording must be done manually by means of stock taking. In solving this problem, the author conducted testing using the black box testing method of the Equivalence Partitions technique. This test is a test carried out by performing random input with certain benchmarks for success. By using a test case design, the author conducts a test to determine whether there is an error in the process of logging into this Inventori application. The expected result of this test is that the system can run well and no errors are found, so that the warehouse department can directly use this application for the process of recording incoming and outgoing goods.